The Contribution of Modern Linguistic Studies to the Development of Arabic Teaching Methods: إسهامات الدراسات اللغوية الحديثة في تطوير طرائق تعليم اللغة العربية - Muhammad Irvan; Nanang Qosim; Abd Faishol (Ukazh : Journal of Arabic Studies, 2025)
This study aims to analyze the conceptual and procedural contributions of modern linguistics in transforming Arabic language teaching methods. While studies on modern linguistics are abundant, a research gap exists where previous research remains predominantly theoretical-descriptive, lacking applicable guidance for classroom practitioners. The novelty of this research lies in the systematic integration of the four pillars of modern linguistics (phonology, morphology, syntax, and semantics) with the development of material selection strategies based on "shuyu'" (frequency of use) and the teacher's role as a linguistic analyst. Employing a library research method with content analysis techniques, data were gathered from primary and secondary literature published between 2012–2025 using strict inclusion criteria. The results indicate that the implementation of modern linguistics shifts the learning orientation from mere grammatical rote memorization to mastering communicative and socio-cultural functions. This study recommends restructuring Arabic curricula based on descriptive linguistic analysis to achieve effective communicative competence.